2012
DOI: 10.1002/asia.201200578
|View full text |Cite
|
Sign up to set email alerts
|

Reaction‐Based Colorimetric and Ratiometric Fluorescence Sensor for Detection of Cyanide in Aqueous Media

Abstract: A stilbene-based compound (1) has been prepared and was highly selective for the detection of cyanide anion in aqueous media even in the presence of other anions, such as F(-), Cl(-), Br(-), I(-), ClO(4)(-), H(2)PO(4)(-), HSO(4)(-), NO(3)(-), and CH(3)CO(2)(-). A noticeable change in the color of the solution, along with a prominent fluorescence enhancement, was observed upon the addition of cyanide. The color change was observed upon the nucleophilic addition of the cyanide anion to the electron-deficient cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Given the obvious ICT character of the first excited state of DBMO, its UV-vis absorption spectra and fluorescence emission spectra distinctly red shifted compared with DBM. 11,52 Thus, DBM is an excellent candidate for a colorimetric and ratiometric fluorescent chemosensor for fluoride anions.…”
Section: First Excited-state Geometries and Sensing Mechanismmentioning
confidence: 99%
“…Given the obvious ICT character of the first excited state of DBMO, its UV-vis absorption spectra and fluorescence emission spectra distinctly red shifted compared with DBM. 11,52 Thus, DBM is an excellent candidate for a colorimetric and ratiometric fluorescent chemosensor for fluoride anions.…”
Section: First Excited-state Geometries and Sensing Mechanismmentioning
confidence: 99%
“…The electrophilic nature of the dicyanovinyl substituent can be modulated by CN À , which interrupts the p-conjugation [35], with its role as a sensing mechanism clarified by a comparison with the spectrum of 1-methyl-7-azaindole [36]. The synthesis of 1 is readily prepared through a condensation of aldehyde 2 with malononitrile in the presence of triethylamine.…”
Section: Design and Synthesis Of Sensormentioning
confidence: 99%
“…Up to now, a mass of ratiometric fluorescent chemosensors have been synthesized by chemists 16,17,[21][22][23][24][25][26][27][28] . It has been demonstrated that they can quantitatively detect bioactive molecules both in vitro and in vivo 17,24,25,[28][29][30] . To the best of our knowledge, attentions are mainly focused on the novel synthesis of fluorescent chemosensors, and most of the sensing mechanisms are based on speculation 17,24,25,[28][29][30] .…”
mentioning
confidence: 99%
“…It has been demonstrated that they can quantitatively detect bioactive molecules both in vitro and in vivo 17,24,25,[28][29][30] . To the best of our knowledge, attentions are mainly focused on the novel synthesis of fluorescent chemosensors, and most of the sensing mechanisms are based on speculation 17,24,25,[28][29][30] . Nevertheless, explorations on the sensing mechanisms of fluorescent chemosensors are also essential to design more effective fluorescent chemosensors.…”
mentioning
confidence: 99%
See 1 more Smart Citation